Strategi Pengembangan Usaha Mikro Kecil Menengah Halim Accu (Battery Automotive Retailer) pada Era Digital untuk Mencapai Daya Saing yang Kompetitif - Mafatikul Huda, Muhammad Rifqi; Mukti, Teguh Lingga; Winarno, Agung (Transpublika Publisher, 2024)
Micro, Small and Medium Enterprises (MSMEs) have a major contribution to the Indonesian economy but have many competitiveness constraints. Halim Accu as one of the MSMEs engaged in the automotive sector needs to improve its competitiveness, especially in digital marketing. The community service aims to help the owner of Halim Accu become more educated in the use of digital marketing. The method used is community service. The results of the assistance include; (1) Implementation of a structured operating system and work procedures in the form of organizational charts and work operational standards. (2) Automation of the transaction system using the point of sales cashier application. (3) Digital marketing through the use of social media and website. (4) Increased human resources competence through internal and external training. (5) Organized accounting system. (6) Optimization of store displays and product displays. (7) Brand and logo legality through the acquisition of Intellectual Property Rights.